The Educational Method in the Perspective of Al-Quran:: A Tafsir Tarbawi Study - Fachrur Razi Amir (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This study is part of an effort to make al-Qur’an the basis of education and effort to see how is the perspective of al-Qur’an on an aspect of education, namely method of education. This kind of study is known as tafsir tarbawi, a construct of quranic interpretation from an educational perspective. The purpose of this tafsir tarbawi is to find the perspective of al-Qur’an regarding the methods of education. The object of study focuses on (Q.S. [16] An-Nahl: 125), (Q.S. [14] Ibrahim: 24-25), and (Q.S. [5] Al-Maidah): 67). In order to find a complete and sufficient understanding of these verses, the author refers to some books of tafsir: tafsir mafatih al-ghaib, tafsir al-munir, tafsir ibn ashoura, and tafsir misbah. Based on the study the meanings and interpretations contained in the tafsir above, it was found that there are several levels of educational methods that can be used according to the conditions of students, namely bilhikmah, mauidzah hasanah, jadal, dharbu al-matsal, and tabligh.